Tinjauan ‘Urf Terhadap Tradisi Nyadran dalam Pernikahan - Rosiana, Ngafiatun; Muslihudin, Muslihudin; Nurhuda, Abid; Syafi'i, Muhammad Imam (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2024)
The Nyadran tradition is currently still an activity that is strongly believed by the community that doing it will bring benefits in the world and the hereafter. On the other hand, if people don't carry out this tradition, people believe it will result in disaster in all forms being passed on to people who don't do it. Including what happened to the people of Depokrejo village, Kebumen during a series of wedding events. The aim of this research is to explain the Nyadran tradition that occurs in Depokrejo village, Kebumen sub-district, Kebumen district and review it in terms of ‘Urf as law in Islam. This research uses qualitative field research methods or field research with an ethnographic approach whose research object is sociocultural. The results of this research state that the Nyadran tradition is carried out by the families of prospective brides and grooms as well as local religious figures by visiting the graves of their ancestors to pray for them and as a manifestation of respect for their ancestors. After visiting the grave, the kenduri event continues which contains worship of Allah SWT by reading dhikr accompanied by caosan. The Nyadran tradition, if viewed from ‘Urf in terms of form, includes Urf Fi'li, then if viewed from ‘Urf in terms of validity it includes ‘Urf Shohih and if viewed from ‘Urf in terms of scope includes ‘Urf Al-Khass.